Strategi Pengelolaan Zakat Pada Badan Amil Zakat Nasional (Baznas) Kota Pontianak - Suradi, Romi; Amalia, Sisi (Jurnal Ilmiah Ekonomi Islam, 2024)
Pontianak City Baznas has a potential zakat revenue of approximately 250 billion. However, the realization of zakat received was only 5.9 billion or only 2.4%. Meanwhile, the number of Muslims in Pontianak City is 511,431 people, but only 91,419 Muslims paid zakat in 2020 or only 17.9%. And in 2020 there was a decrease in zakat receipts of around 1.1 billion and a decrease in the number of muzakki by around 34,000 people. This research aims to find out what factors hinder and support the zakat management strategy in the Pontianak City Baznas and how to optimize the zakat management strategy in the Pontianak City Baznas. This type of research uses a descriptive quantitative approach. The types of data used are primary and secondary data. The data collection techniques used were observation, interviews, questionnaires and documentation. The analysis method used is SWOT analysis (Strengths, Weaknesses, Opportunities and Threats). The results of the analysis show that the main inhibiting factor in zakat management in Pontianak City Baznas is that Baznas has not been able to reach all muzakki in Pontianak City and many new zakat management institutions have been established that have the same role. Meanwhile, the main supporting factor for zakat management at Baznas Pontianak City is the existence of Baznas which is supported by law and the majority of the people of Pontianak City are Muslims. Pontianak City Baznas is in quadrant I (Aggressive Strategy), namely Pontianak City Baznas is in a strong condition and has opportunities, so it is very possible to continue to expand, increase potential and receive maximum zakat. The strategy for managing zakat at the Pontianak City Baznas to be optimal is by increasing the socialization of zakat to all levels of society, increasing the formation of UPZs in mosques, surau-surau and agencies in Pontianak City, collaborating with zakat management institutions and zakat institutions. newly established in Pontianak City, carrying out new innovations in the zakat program, optimizing the database, and developing a zakat payment system using current trending technological media.